Membangun Karakter Disiplin, Jujur dan Cermat Melalui Model Explisit Instruction Berbantuan Matrik Assesment - Ermaviati, Dwi; Sulistyorini, Wahyu (Jurnal Nispatti, 2024)
The purpose of this report is to describe the implementation and implementation of an explicit instruction model using an assessment matrix to build discipline, honesty, and carefulness in students in the productive subject of Facial Care with Technology. This report was prepared using an empirical descriptive method during practical teaching in grade XII of Skin Care at SMK Negeri 1 Sewon. The data collection method used matrices, questionnaires, observation sheets, documentation, photos, and videos. The preparation of this report is also based on character education planning, namely: planning, implementation, evaluation, and follow-up activities. The application of the assessment matrix in the practical subject of facial care with technology is able to build discipline, honesty, and carefulness in students. The results obtained from its implementation showed that the character of discipline had not yet developed in students, honesty and carefulness began to develop after this activity. As a follow-up to the learning outcomes, students should be accustomed to it by providing a self-assessment checklist for each lesson so that students can control themselves without being asked by the teacher. This assessment matrix can be developed in all practical subjects.